Pengembangan Media Pembelajaran Komponen Aktif dan Pasif Berbasis Barcode Pada Matapelajaran Dasar Listrik dan Elektronika di SMK N 3 Negara - Angga Prasetya; I Putu Suka Arsa; I Gede Made Surya Bumi Pracasitaram (Universitas Pendidikan Ganesha, 2022)
This study aims to create a Barcode-Based Active and Passive Component Trainer Learning Media at SMK Negeri 3 Negara. This research is classified as R&D (Research and Development) research. This study uses a statistical analysis method used to process percentages of content experts, media experts, and field trials. This study used a questionnaire as an instrument for collecting data from content experts, media experts, and students. The research results obtained: the results of the media expert test got a percentage of 98.33% with very decent qualifications, and the content expert validation test got a percentage of 96.66% with very decent qualifications. The score range for all 5 small group test respondents is listed in very high qualification, and the score range for all 10 large group test respondents is listed in very high qualification. Barcode-Based Active and Passive Component Trainer Learning Media at SMK Negeri 3 Negara is suitable for use in the learning process.